THE IMPROVEMENT OF SELF CONCEPTUAL AND THE ABILITY OF KNOWING LIFE'S PURPOSE OF TEENAGER PRISONER WITH LOGOTHERAPY - Dwi Heppy Romchmawati; Betie Febriana; Prasetyo Aji Nugroho (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2014)
Introduction: The number of juvenile prisoners who has found at the first class prison institution in Semarang is 25 people. This figure shows that increasing around 20% in compare with the previous year. Juvenile prisoners who have experienced disorder of self-concept caused in an inability in make sense of their life. The aim of this research is to describe the implementation effect of logotheraphy to the self-concept and the ability to make sense of life to the juvenile prisoners at first class prison institution in Semarang. Logotherapy is a technique to cure or reduce or alleviate the existential crises through the discovery of the meaning of life. Logotherapy is implemented in the form of counseling and oriented individual to find the meaning of life. Method: This research uses a design Quasy experiment with methods of pretest and post test in one group. Results: The results of research showed no significant effect on self-concept logotherapy with p value > α is 0.167. But there was a significant effect of the meaningfulness of life logotherapy with p value < α is 0.035. Discussion: Based on the above results that logotheraphy need to be recommended that can be used as a standard therapy for nursing specialist in finding the meaning of life. Keywords: logotherapy, self-concept, Quasy experiment, pre and post-test one group